Conservative compensatory Angle Class III malocclusion treatment - Marcio Costa Sobral; Fernando Antônio de Lima Habib; Liz Matzenbacher (Dental Press Journal of Orthodontics, 2012)
INTRODUCTION: Angle's Class III malocclusion is a dental discrepancy in a sagittal view that may appear or not with an important skeletal discrepancy. Facial esthetics may be affected by this skeletal discrepancy and it is one of the most common complaints of patients who seek orthodontic treatment. Class III treatment, in adults, may be done by compensatory tooth movement, in simple cases, or through an association between orthodontics and orthognathic surgery, in more severe cases. OBJECTIVE: This article describes a non-extraction compensatory Class III treatment case, applying the Tweed-Merrifield mechanical principles with headgear (J-Hook) in the mandibular arch. This case was presented at the V Brazilian Association of Orthodontics and Dentofacial Orthopedics (ABOR) Meeting, it was evaluated by members of Brazilian Board of Orthodontics and obtained third place in the general classification. INTRODUÇÃO: a má oclusão de Classe III se caracteriza por uma desarmonia dentária anteroposterior, podendo estar ou não acompanhada por discrepâncias esqueléticas. A estética facial pode se apresentar comprometida, em maior ou menor grau, a depender da magnitude da discrepância, constituindo um dos principais fatores motivadores da procura por tratamento ortodôntico. O tratamento da Classe III em pacientes adultos pode ser realizado mediante compensação dentária, nos casos mais simples, ou, em situações mais severas, mediante a associação entre Ortodontia e Cirurgia Ortognática. OBJETIVO: o presente artigo objetiva relatar um caso clínico caracterizado por uma má oclusão de Classe III de Angle, tratado de forma compensatória, com extração dos terceiros molares inferiores, mediante a utilização de aparelhagem extrabucal na arcada inferior (J-hook), aplicando-se princípios da técnica de Tweed-Merrifield. Esse caso foi apresentado no 5º Congresso da Associação Brasileira de Ortodontia e Ortopedia Facial (ABOR), na categoria "mesa clínica", sendo avaliado por membros do Board Brasileiro de Ortodontia e Ortopedia Facial (BBO) e obtendo o terceiro lugar na classificação geral.